(untitled) (Research, Society and Development, 2020)
This article is an excerpt from a thesis that argues that nursing students select nursing interventions based on a fundamental patterns of knowledge in nursing. The objectives were: to identify and classify the predominantly personal knowledge that undergraduate students use to select nursing interventions. It is a descriptive, exploratory study with a qualitative approach, outlined by the Fundamental Patterns of Knowledge in Carper’s Nursing. The chosen scenario was a nursing higher education school from a public university in Rio de Janeiro. Ten students from the sixth period participated. Data were collected through non-participatory observation and semi-structured interviews and, subsequently, submitted to content analysis. The results were categorized as follows: ’I know what I know? ’’ Do I do what I know?’. It can be concluded that the patterns of personal knowledge was one of the pillars used by students to select the nursing interventions necessary to serve the person they care for.